Measurements of the ambient dose equivalent rates around the Manyoni uranium deposit in Tanzania (Brazilian Journal of Radiation Sciences (BJRS), 2023)
In this study, pre-mining ambient gamma dose equivalent rates at 1 m above the ground were measured using a Gamma-Scout portable radiation survey meter at two sites, A and B, around the Manyoni uranium deposit in Tanzania. Site A is expected to receive mine-dust particles with an aerodynamic diameter ≤ 10 µm (PM10) that have mean annual ground level concentrations (AGLC) ≥ 10% of the WHO air quality guideline limit of 20 µg/m3, and Site B is expected to receive PM10 with a mean AGLC ≥ 20 µg/m3. At Site A, the average of the ambient dose equivalent rates was 0.25 ± 0.03 µSv/h and ranged from 0.08 to 0.69 µSv/h. Similarly, at Site B, the average of the ambient dose equivalent rates was 0.23 ± 0.02 µSv/h and ranged from 0.12 to 0.34 µSv/h. The effect of the local geology on the measured dose rates was also presented. Since the ambient dose equivalent is an operational quantity for area monitoring, the results of this study will be very useful for comparing with the operational monitoring results of Sites A and B once uranium mining starts in Manyoni. This can help mine operators and regulatory agencies keep an eye on any rise in background radiation so they can take the necessary measures to safeguard locals and the environment from the harmful effects of ionising radiation.